Addressing the social aspect of high workforce turnover : human capital management strategies at Alpha Group - Nguyen Thuy Linh; Levermore, Roger; Shah, Faiz H.; Brubaker, Richard (Pathumthani,Thailand : Asian Institute of Technology, 2025)
This study primarily examines the key variables leading to elevated employee turnover at Alpha Group in 2023. Referencing best practices from the Human Resource Management (HRM) model and Human Capital Development (HCD) strategies of multinational organizations, I assess the efficacy of Alpha's existing HRM and HCD in relation to employee retention and adaptation with the group's future requirements. I also examine the correlation between CSR activities and ESG initiatives on employee retention.My research indicates that sustainable human capital management strategies, including competitive remuneration and sufficient healthcare benefits, are critical factors in employee recruitment and retention. I observe a positive correlation between the corporate culture that fosters work-life balance and employee retention. However, Alpha's human capital development plan should be revitalized, emphasizing education, training, and skill-building to enhance not only the company{u2019}s staff productivity but also promote economic and social mobility through partnerships with universities and vocational training for underprivileged communities and skill development for workers in jobs affected by automation. Alpha{u2019}s employees should actively participate in CSR activities, and the company{u2019}s ESG initiatives should be broadened and incorporated into performance evaluations. Furthermore, Human Resources should operate as a proactive and strategical partner with Business in human capital investment.In light of the findings, this study aims to provide initial recommendations that emphasize solutions for enhancing employee engagement with Alpha's CSR activities, alongside a training and development framework designed to meet the future workforce needs of Alpha and to maximize societal benefits.
A project report submitted in partial fulfillment of the requirements for the degree of Professional Master in ESG (Environment-Social-Governance) Management
Keywords: Human capital -- Vietnam -- Management; Human capital -- Vietnam -- Social aspects; Personnel management -- Vietnam -- Case studies; Social responsibility of business